Retroperitoneoscopic Resection of a Lumbosacral Plexus Schwannoma: Case Report and Literature Review - Freitas, Bruno; Figueiredo, Rui; Carrerette, Fabrício; Acioly, Marcus André (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Study Aims Schwannomas are benign tumors derived from the Schwann cells of the peripheral nerve sheath that rarely affect the retroperitoneum. When symptomatic, surgical resection is usually recommended via open surgery or the laparoscopic transperitoneal approach. We discuss the retroperitoneoscopic resection of lumbosacral plexus schwannomas through an illustrative case and literature review. A new management classification is also proposed.Patients A 61-year-old woman affected by schwannomatosis presented with neuropathic pain in her right inguinocrural area for the past 4 years before admission. Preoperative imaging revealed a 2-cm right retroperitoneal tumor lateral to the psoas muscle. The diagnosis of a schwannoma of the ilioinguinal nerve was then suggested. The patient underwent complete tumor resection through retroperitoneoscopy, and no recurrence was observed over the long term. A review of the relevant literature revealed that surgical strategy depends on tumor location, and therefore patients are divided into three groups by tumor position to guide trocar placement: type 1 (paravertebral or over the psoas muscle), type 2 (lateral to the psoas muscle), and type 3 (sacral or pelvic).Results Four patients were classified as type 1, one as type 2, and three as type 3, thereby guiding trocar placement to a lateral, anterior, or inferior montage, respectively.Conclusions Retroperitoneoscopy is a minimally invasive technique that offers some potential advantages in approaching retroperitoneal masses. This new classification is useful to group patients and thus provide guidance on the best retroperitoneoscopic surgical strategy.
Keywords: lumbosacral; retroperitoneoscopy; schwannoma; tumor